TEACHERS’ STRATEGIES IN CORRECTING STUDENTS’ ERRORS IN CLASSROOM INTERACTION - Yeasy Agustina Sari (Jurnal Pedagogy, 2016)
This research was aimed to investigate the strategies used by the teachers in correcting the students’ errors in classroom interaction. The research was conducted at ten States Junior High Schools of Payakumbuh, West Sumatera consisted of one classroom for each school. The subject of the research was the ten teachers and all the students who were exist in those ten classrooms. This research was descriptive qualitative with the classroom interaction analysis. The finding of this research were (1) the errors which most frequently made by the students were vocabulary error. (2) The teacher used some different strategies in correcting the students’ error. However, the strategies which the most frequently used were explicit correction and recast. (3) The students’ preference was on explicit correction, metalinguistic feedback and clarification request. (4) The commonly reason of teachers tend to use the certain strategies in correcting the students’ error was because the teacher consider that the oral error correction was the effective way to communicate and help the students improve their speaking skill. Besides, the teachers know the level of students’ understanding, condition, and the ability in receiving what the teachers gave.